Application of spin-crossover water soluble nanoparticles for use as MRI contrast agents. Issue 1 (December 2018) - Tsukiashi, Asami; Min, Kil; Kitayama, Hikaru; Terasawa, Hiroaki; Yoshinaga, Sosuke; Takeda, Mitsuhiro; Lindoy, Leonard; Hayami, Shinya
Abstract Water soluble spin-crossover (SCO) iron(II) nanoparticles (NPs) were synthesized by the polyethylene glycol (PEG) coating of [Fe(Htrz)3-3× (NH2 trz)3× ](BF4 )2 (x = 0, 0.1, 0.5 and 1). The NPs with x = 0.1 show gradual SCO behavior over 280–330 K in water. The relaxation times, T 1 andT 2, were determined and the thermally-responsiveT 2 values making these NPs a candidate for use as a MRI contrast agent.